Case Report: Depression × dementia with Lewy bodies in the elderly: The importance of differential diagnosis - Valença, Alexandre M.; Studart Leal, Cláudia Cristina; Oliveira, Gustavo C.; de Moraes, Talvane M.; Nardi, Antonio E.; Mendlowicz, Mauro V. (Frontiers in Psychiatry, 2022)
Background: Dementia is a clinical syndrome which is more common in elderly people. Dementia with Lewy bodies (LBD) is not so rare in elderly people, with cognitive impairment in about 30% over age 65. The clinical picture is characterized by fluctuation in cognitive functions, recurrent, well-formed, detailed visual hallucinations, and Parkinsonism, with rigidity, tremor, bradykinesia, and slurred speech. Case Presentation: We present a case report of LBD in a 73-year-old retired teacher, whith a initial wrong diagosis of refratary Depression for at least 3 years. We also conduct a review of recent works on theme. Conclusion: LBD diagnosis can be neglected for years, with a legal and clinical issues to patients and their families. Detailed medical research, including differential diagnosis, are very necessary on those cases, specially when they are called refratary. We encourage new research and adequate clinical training to prevent damage.